Optimizing the Waste Bank Mapping Management Information System in Batam City - Hidayat, Fendi; Nugraha, Nur Budi (Politeknik Negeri Batam, 2023)
Geographic Information Systems (GIS) have been widely applied in environmental health, including determining the locations of waste banks. Currently, in Batam City, there is no mapping-based system available to track the distribution of waste banks, posing challenges for residents to access information about nearby waste bank locations. Population growth is correlated with rising household demands, including the need for food, clothing, and housing. People need their basic necessities to survive. The industries of manufacturing, transportation, healthcare, and communication have all seen significant advancements since the Industrial Revolution. With the advent of information and technology (IT), all of those areas' development in the 19th and 20th centuries was larger and faster. Hence, this study introduces a management information system with mapping technology for waste banks in Batam City. Employing a descriptive analysis approach, the software development follows the waterfall method, and Unified Modeling Language (UML) serves as the design tool. The resulting system proves effective in providing information on Waste Bank locations and assisting administrators in managing Waste Bank location data.